The effect of educational aspirations on labor market outcomes in secondary vocational education in Africa - Oyeronke Christiana Paramole; Moses Adeleke Adeoye (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2024)
The study explores the relationship between educational aspirations and labour market outcomes among African secondary vocational education students. It reveals that students with vocational education are more aware of labour market demands and desire to acquire skills that align with industry needs. However, disparities in access to quality vocational training and societal perceptions of vocational education significantly impact students' aspirations. A comprehensive systematic literature review was explored to examine the impact of educational aspirations on labour market outcomes in secondary vocational education in Africa, focusing on countries like Nigeria and Ghana. The review focuses on studies published between 2010 and 2024, reflecting current trends and challenges vocational education graduates face. The study identifies key labour market outcomes linked to vocational education, including employment rates, job stability, and income levels. Graduates of vocational programs secure employment more rapidly than general education students but face challenges in advancing their careers due to limited opportunities for further training and professional development. The research calls for policy interventions to enhance the quality and perception of vocational education in Africa, ensuring that they meet immediate labour market needs and empower young people to achieve their long-term career aspirations. This research can potentially inform vocational education policy in Africa by developing targeted strategies to enhance the effectiveness of vocational training programs. Adapting policies that align vocational education with labour market demands can create a more responsive educational system that addresses the needs of both students and employers.